الحوكمة المؤسسية المصرفية ومدى توافر دعائمها للوقاية من ألأزمات المالية في المصارف العراقية الخاصة المقيدة بسوق العراق للأوراق المالية (Journal of Accounting and Financial Studies ( JAFS ), 2011)
Growing interest in the subject of corporate governance after the repercussions of financial collapses of some of the leaders of American companies and European, and the consequent crisis of confidence in global financial lists of companies due to weak accounting disclosure and transparency, was quick from many countries and international organizations to adopt the concept in an attempt to improve the situation of companies and promote transparency and prevent further financial crises in the future. Based on this background, the present study aims to shed light on the concept of exercising the powers of governance that has become invitations for adoption in Iraq of great importance, given the increasing role of corporations both restricted and unrestricted in the Iraqi market for securities, focusing on the situation of Iraqi private banks to the need for follow-up performance and access to the best level of performance in improving efficiency and economic and financial stability. The study showed that corporate governance of the banking system is nothing but a system through which management and control of banks in order to protect shareholder rights, equality, justice, involvement  them in decision-making , the provision of information in a transparency information transparency, clarity and determine the responsibility of board members and their rights. The findings of the study that, despite the novelty of the concept of corporate governance of banks in the Iraqi environment but there are serious attempts to define the mechanisms and implementation mechanisms on the ground. And that the departments of private Iraqi banks play a vital role in the application of the concept as act as liaison between regulatory agencies and the Governing Council.